САМОСТІЙНИЦЬКИЙ ТРАНЗИТ ЗАПОРІЗЬКОЇ ПАРТІЙНО0РАДЯНСЬКОЇ НОМЕНКЛАТУРИ 1991 РОКУ (Zaporizhzhia Historical Review, 2021)
Zaporizhzhja region, typical for South-East part of Ukraine, serves as an example for researching the adaptation process of Soviet party elite, which has been formed in communist conditions, for new political reality that started appearing in Ukraine after its independence proclamation in August 1991. The state of population’s mass consciousness and political forces balance, in the result of which the old administrative apparatus remained at power, and social-political consequences of its process are analyzed.